2022
DOI: 10.17159/sajs.2022/13497
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties of porous activated carbon prepared from palm kernel shell through a low-cost activation protocol

Abstract: Biomass-promoting routes for the synthesis of activated carbon (AC) have recently received considerable attention due to the advantages of this method: it is simple, cost-effective, and ecofriendly. This method is also an alternative way to avoid the unsafe practice of waste incineration. We describe the preparation of activated carbon from palm kernel shell (PKS) – an abundant biomass that is available in Africa and Asia. We investigated the effect of process variables such as impregnation ratio (ratio of H3P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Zhang et al [30] developed an H 3 PO 4 activated hydrochar derived from peanut hull and showed that chemical modi cation greatly increases the adsorption capacity of hydrochar compared to acetone and cyclohexane. Pam et al [31] used palm kernel shell chemically to synthesize activated carbon and investigated the effect of process variables (ratio of H 3 PO 4 to PKS) and carbonization temperature on microstructure performance, morphology, pore structure and adsorption properties for methylene blue and iodine. Haghbin et al [32] prepared highly-porous activated carbon from date palm bark by chemical activation method with phosphoric acid and after characterization con rmed that date palm bark can be considered a cheap and promising precursor for the commercial preparation of activated carbon.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [30] developed an H 3 PO 4 activated hydrochar derived from peanut hull and showed that chemical modi cation greatly increases the adsorption capacity of hydrochar compared to acetone and cyclohexane. Pam et al [31] used palm kernel shell chemically to synthesize activated carbon and investigated the effect of process variables (ratio of H 3 PO 4 to PKS) and carbonization temperature on microstructure performance, morphology, pore structure and adsorption properties for methylene blue and iodine. Haghbin et al [32] prepared highly-porous activated carbon from date palm bark by chemical activation method with phosphoric acid and after characterization con rmed that date palm bark can be considered a cheap and promising precursor for the commercial preparation of activated carbon.…”
Section: Introductionmentioning
confidence: 99%